Large-scale industrial plantations are more likely than smallholdings to threaten biodiversity from oil palm replanting spatial disturbances - Azhar, Badrul; Oon, Aslinda; Lechner, Alex M.; Ashton-Butt, Adham; Yahya, Muhammad Syafiq; Lindenmayer, David B. (Elsevier, 2023)
Certification has advanced efforts to increase the environmental sustainability of oil palm agriculture. However, there is little consensus among stakeholders on what type of farming system should be employed to enhance the environmental sustainability of the oil palm supply chain. Replanting of oil palm has increased as a result of commitments to reduce deforestation and the need to replace ageing plantations. In the next 10–20 years, ∼ 24 million ha of large-scale industrial plantations and smallholdings will be replanted across the tropics. Evidence from previous studies indicates there are adverse impacts of large-scale oil palm replanting on biodiversity. Here we compared the size of replanting in smallholdings and large-scale industrial plantations using open source satellite images. We then made predictions about their possible environmental effects of oil palm replanting. Using Google Earth Pro, we calculated five landscape metrics at 865 replanted fields: size, perimeter, shape index, minimum and maximum distance from a centroid of a planted field to the boundary of the field. These metrics most likely represent how spatial cover affects animal distribution and movement in oil palm production landscapes. In addition, 52 local birders were polled about their perceptions of impacts of oil palm replanting on native birds. We found that the landscape metrics for replanting in smallholdings were lower than those calculated for large-scale industrial plantations. Most local birders thought that replanting oil palm in industrial plantations had a greater detrimental effect on native bird species (21 versus 10 respondents) than replanting on smallholdings. In addition, local birdwatchers considered replanting oil palm on smallholdings to be more neutral (21 versus 29 respondents) and beneficial (11 versus 12 respondents) for birds than replanting in industrial plantations. Our findings suggest that the biodiversity impacts of oil palm replanting on smallholdings will be less severe than on large-scale industrial plantations. We recommend plantation businesses use replanting techniques comparable to smallholdings. The findings reported here may help industry stakeholders mitigate the negative environmental consequences of oil palm replantings on farmland and forest biodiversity.